Congenital block vertebrae and intervertebral disc protrusion in a young cat. Issue 2 (August 2019) - Crowe, Yvette C; Child, Georgina; Lam, Richard; McGregor, Ross
Case summary: A 6-month-old domestic shorthair cat was evaluated for proprioceptive ataxia of the pelvic limbs. Over 2 months, the cat became poorly ambulatory, paraparetic with proprioceptive ataxia and developed a firm, distended bladder with intermittent overflow urinary incontinence. Block vertebrae (T1–3, T4–5 and T10–11) and lordosis were identified on radiographs of the vertebral column. MRI revealed T3/4 intervertebral disc protrusion with severe extradural compression, secondary syringohydromyelia caudal to the protrusion and generalised intervertebral disc disease throughout the cervical and thoracic vertebrae. Dorsal laminectomy at T3/4 resulted in resolution of paraparesis and marked improvement in coordination and strength. Block vertebrae are usually considered an incidental finding. In this patient, angular deformation (lordosis) and adjacent segment disease probably contributed to clinically significant intervertebral disc degeneration and protrusion. Relevance and novel information: There are few case reports in the literature of multiple congenital vertebral malformations causing neurological deficits in cats. This is the first reported case of successful surgical management of intervertebral disc protrusion, possibly secondary to block vertebrae and lordosis in a cat.